In vitro evaluation of antibacterial activity of an herbal dentifrice against Streptococcus mutans and Lactobacillus acidophilus - Vyas Yogesh; Bhatnagar Maheep; Sharma Kanika (Wolters Kluwer Medknow Publications, 2008)
Antibacterial activity of a herbal dentifrice Arodent against Streptococcus mutans and Lactobacillus acidophilus was evaluated using Colgate ® as standard. Both bacterial strains were isolated from the oral cavity on selective media and identified by standard methods. The antibacterial activity was assayed by cup-well method. The bacterial lawn of facultative anaerobe S. mutans was established between two layers of agar under microaerophilic conditions. Five and a half millimeters and 10 mm zones of inhibition were produced by Arodent against S. mutans and L. acidophilus , respectively, under microaerophilic conditions. On the other hand, the standard dentifrice Colgate produced 5.83 mm and 10.17 mm zones of inhibition against S. mutans and L. acidophilus , respectively, under microaerophilic condition. The results suggest that Arodent is an effective antibacterial herbal dentifrice.